Discover a wealth of knowledge at Westonci.ca, where experts provide answers to your most pressing questions. Join our platform to connect with experts ready to provide detailed answers to your questions in various areas. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
Let [tex]S_n[/tex] be the [tex]n[/tex]-th term in this sequence, so
[tex]S_1 = 1[/tex]
[tex]S_2 = 1 + 2[/tex]
[tex]S_3 = 1 + 2 + 2^2[/tex]
and so on, with general [tex]n[/tex]-th term
[tex]S_n = 1 + 2 + 2^2 + \cdots + 2^{n-1} = \displaystyle \sum_{i=1}^n 2^{i-1}[/tex]
Observe that
[tex]2 S_n = 2 + 2^2 + 2^3 + \cdots + 2^n[/tex]
and by subtracting this from [tex]S_n[/tex], we eliminate all but the outermost terms, namely
[tex]S_n - 2S_n = 1 - 2^n[/tex]
so that
[tex]-S_n = 1 - 2^n[/tex]
[tex]S_n = 2^n - 1[/tex]
Now, the sum of the first [tex]n[/tex] terms of the sequence [tex]\{S_1,S_2,S_3,\ldots,S_n\}[/tex] is
[tex]S = S_1 + S_2 + S_3 + \cdots + S_n[/tex]
[tex]S = \displaystyle \sum_{i=1}^n S_i[/tex]
[tex]S = \displaystyle \sum_{i=1}^n (2^i - 1)[/tex]
[tex]S = \displaystyle \sum_{i=1}^n 2^i - \sum_{i=1}^n 1[/tex]
[tex]S = \displaystyle 2 \underbrace{\sum_{i=1}^n 2^{i-1}}_{S_n} - n[/tex]
[tex]S = 2(2^n - 1) - n[/tex]
[tex]S = \boxed{2^{n+1} - n - 2}[/tex]
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.